Development of a real-time vibration monitoring system for drum tester machines using ADXL345 sensor and ESP32 microcontroller - Herdiansyah Noorrizky Anggana; Moch Solikin (Universitas Negeri Yogyakarta, 2025)
This study focuses on developing a vibration level monitoring system for a drum tester machine, utilizing the ADXL345 sensor in conjunction with the ESP32 microcontroller and a web-based monitoring platform. The system was implemented at PT Astra Daihatsu Motor's Sunter Assembly Plant (SAP) located in Jakarta, Indonesia, for large-scale industrial use. The design aimed to boost precision in vibration monitoring and elevate workforce productivity. The sensor collects data, which is then sent to a MySQL database and shown in real-time on an LCD and through a Grafana-based web interface. Functional tests verified that all components performed as specified. The ESP32 microcontroller provided reliable Wi-Fi connectivity, and the ADXL345 sensor showed impressive accuracy in detecting vibration changes in both static and dynamic situations. Performance tests conducted over eight hours, with data collected at one-minute intervals, demonstrated consistent readings across all axes (X, Y, Z), highlighting the system's reliability. The implementation of this system resulted in enhanced efficiency in machine monitoring. The inspection interval has been extended from two weeks to one month, which has reduced the workforce requirements from two workers to one. Moreover, the time required for inspection was reduced from 20 minutes to only one minute. To summarize, this vibration monitoring system enhances the accuracy of real-time data, improves workforce efficiency, and ensures reliable monitoring of machine conditions. This offers a creative approach for industrial uses, enhancing operational efficiency and ensuring workplace safety.